2003
DOI: 10.1177/0143034303024002001
|View full text |Cite
|
Sign up to set email alerts
|

Bullying and the Big Five

Abstract: Research on the social context of bullying includes children who help the victim, assist the bully or remain outsiders. 96 children from two public schools in Central Italy were classified according to an Italian version of the Participant Role Scale (Sutton and Smith, 1999) as Defenders of the Victim, Outsiders, Victims or Pro-bullies. Teacher reports indicated Friendliness and Emotional Instability as the strongest distinguishing personality factors among the participant roles, followed by Conscientiousness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
1
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(55 citation statements)
references
References 38 publications
6
35
1
7
Order By: Relevance
“…Hence, it is possible that not specific anxiety for mathematics but rather a more generalized, unspecific anxiety affects self-concept formation. A small number of studies have related neuroticism to poorer school adjustment and poorer peer relationships at school (Lamb, Chuang, Wessels, Broberg, & Hwang, 2002) and a higher likelihood of victimization (Tani, Greenman, Schneider, & Fregoso, 2003). The present study provides us with further insights into the difficult academic life of emotionally unstable students.…”
Section: Mathematics Self-conceptmentioning
confidence: 57%
“…Hence, it is possible that not specific anxiety for mathematics but rather a more generalized, unspecific anxiety affects self-concept formation. A small number of studies have related neuroticism to poorer school adjustment and poorer peer relationships at school (Lamb, Chuang, Wessels, Broberg, & Hwang, 2002) and a higher likelihood of victimization (Tani, Greenman, Schneider, & Fregoso, 2003). The present study provides us with further insights into the difficult academic life of emotionally unstable students.…”
Section: Mathematics Self-conceptmentioning
confidence: 57%
“…In all studies that measured it, psychoticism was related to bullying others (Connolly & O'Moore, 2003;Mynard & Joseph, 1997;. In all studies that examined the Big Five model, agreeableness was negatively related to bullying either for all bullies (Bollmer et al, 2006;Tani et al, 2003) or only for pure bullies (Turner & Ireland, 2010). Openness was not associated with bullying in any of the studies.…”
Section: Introductionmentioning
confidence: 85%
“…To date, six school-based studies (Bollmer, Harris, & Milich, 2006;Connolly & O'Moore, 2003;Farrington & Baldry, 2010;Mynard & Joseph, 1997;Tani, Greenman, Schneider, & Fregoso, 2003) and one prison-based study (Turner & Ireland, 2010) have examined the relationship between structural models of personality and bullying. 4 Although not directly comparable, the above-mentioned seven studies reported some consistency in the way that personality traits relate to bullying.…”
Section: Introductionmentioning
confidence: 99%
“…Children who defend appear to have healthier self-esteem than children in other roles ), more favorable academic and emotional self-concept (Salmivalli 1998), and more social self-efficacy (Gini et al 2008). Tani, Greenman, Schneider, and Fregoso (2003) found that children identified as defenders score higher than children in all other roles on trait agreeableness, which includes trait altruism. Finally, nine out of the 13 studies examined that directly consider defending behavior find boys to be underrepresented among children who defend as compared to girls (Goossens et al 2006;Menesini et al 2003;Salmivalli et al 1996Salmivalli et al , 1998Salmivalli et al , 1999Salmivalli et al , 2005Salmivalli and Voeten 2004;Sutton and Smith 1999), though results are mixed in one study (Sutton and Smith 1999).…”
Section: Individual Tendencies and The Defender Rolementioning
confidence: 93%